LOWITA COASTAL COMMUNITIES: A QUALITATIVE ANALYSIS OF MARINE TOURIST DEVELOPMENT FOR LOCAL ECONOMY IMPROVEMENT - S, Andi Bahri; Rahman, M. Nur; Soumena, Moch. Yasin; Syarifuddin, Mustika; Putra, Adhitia Pahlawan (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
The community participation in developing marine tourism industry in turtle conservation areas is important. However, in fact, that turtles are caught and traded for human consumption. The research aims are to analyze the forms of community participation in developing marine tourism in the turtle conservation areas and what are the factors hindering the participation of Lowita communities in Suppa, Pinrang Regency. This research applies descriptive qualitative used a phenomenological approach. The data collection techniques were observation, interviews and documentation. The research findings shown that local community participation in the Lowita Beach turtle conservation area is included in the interactive participation category, prevented by the community in direct turtle conservation area, in such participating in outreach activities and building facilities in the turtle conservation area. Meanwhile, the inhibiting factor faced by the Lowita people, specifically of Wiringtasi Village was cultural barriers, which can be seen from the lack of quality human resources regarding the tourism business industry. In addition, differences in views and habits of local residents tend to hinder turtle conservation. Local residents have long viewed turtles as a resource to be consumed as a substitute for the family economy; this does not support the turtle conservation that is being promoted